Europe cracks down on e-waste.
Electronic waste in Europe is growing so fast that it will double between 1998 and 2010, according to European Union documents. And in 1998 it already measured in the region of six million metric tons. The pace of its accumulation worries public officials because e-waste contains lead and other chemicals that can leak into water supplies. As consumers and businesses dump their old computers, regulators are scrambling to steer machines and their parts out of landfills. While this spreading scrap threatens towns around the world, the European Union is preparing a broad response. It will soon issue a Waste from Electrical and Electronic Equipment (WEEE) directive, requiring manufacturers to take machines back for free and to recycle 65 percent of their average weight. The European Parliament passed the directive on 10 April, 2002, one step in the process. Member states of the union will soon consider it; they could ratify the directive, which is akin to law, as early as fall 2002. WEEE is set to take full effect by 2008
Keywords: EU manufacturers; European Parliament; European Union; Waste from Electrical and Electronic Equipment directive; Computers; E-waste.; Electronic waste; Lead; Recycling; Water supplies contamination